Research methodology, description of action and the application of Laser Doppler flowmeter to dentistry - Wieczorek, Paulina; Rudzki, Marcin; Drohomyretska, Myroslava; Klichowska-Palonka, Małgorzata (Journal of Stomatology, 2015)
Introduction. Laser Doppler Flowmetry (LDF) is a non-invasive method of assessing blood flow in the vascular bed in real time, which has a wide range of applications to medicine and dentistry. The device uses the Doppler Effect. The emitted monochromatic light is dissipated in the tissues; a part of the beam, which is reflected from moving parts, changes the wavelength of the light. The reflected beam returns to the unit, where the spectrum of the reflected light is analyzed in terms of distribution of wavelengths. On this basis, the quantity and speed of moving parts are assessed in the tissue. In medicine, Doppler flowmetry is used to evaluate changes in microcirculation. In dentistry, it has its application to dental traumatology, prosthodontics, periodontics, orthodontics, oral and maxillofacial surgery. The aim of the study is to provide the information on the action of Laser Doppler flowmeter, present research methodology and the use in dentistry based on previous studies. Results. Early detection of lesions in microcirculation enables early warning and monitoring of the processes ongoing in the vascular bed. LDF offers the possibility of entering the microcosm vessels without the violation of tissue continuity. It should be remembered that Laser Doppler flowmetry requires careful compliance with the test protocol in order to eliminate artefacts that affect test results.